Description of larvae of two closely related species Cassida palaestina Reiche, 1858 and Cassida rubiginosa Müller, 1776 (Coleoptera: Chrysomelidae: Cassidinae) - Świętojańska, Jolanta; Moradian, Hossein; Borowiec, Lech; Ostovan, Hadi (Zootaxa, 2013)
Larvae of two closely related species Cassida palaestina Reiche, 1858 and Cassida rubiginosa Müller, 1776 are described in detail including SEM microstructures. First instars are extremely similar with no clear diagnostic characters, larvae of Cassida palaestina are slightly more contrastingly coloured than larvae of C. rubiginosa, the latter having darker scoli, basal part of supra-anal processes and legs. Last instars differ in very subtle but constant characters: lateral scoli of                C. palaestina are slightly shorter than those of C. rubiginosa, in C. palaestina tops of the lateral branches are armed apically with an elongate cauliflower-shaped sensillum while in C. rubiginosa tops of the lateral branches are more often armed with a pointed seta than with an elongate cauliflower-shaped sensillum, and cauliflower-shaped sensilla on tergites are less elongate in C. palaestina than in C. rubiginosa. These differences accompanied by distinguishing characters of adults and their distribution range indicate that both taxa are probably vicariant species with partial parapatric occurrence. Centaurea behen is a new host plant for C. palaestina.